Infant learning platform using Arduino (project 2) - Xie, Shiqi (Nanyang Technological University, 2020)
Early childhood learning is vital for human development. Color and shape are two fundamentals on facilitating a toddler's visual discrimination skills, while the most stimulating method of early childhood learning is through sound and visual cues. The objective of this final year project is to design and develop an educational and customizable product prototype focused on color and shape understanding enhancement. Using an Arduino platform, toddlers can smoothly input to the toy, while parents can take the output through the customizable mobile application. This report is comprised of five chapters, which starts with an overview of color and shape understanding of early childhood education and final year project introduction. Literature review section clarifies the visual discrimination skills of children and previous studies. The following chapters elaborate on the methodology and implementation of the learning platform. The summary and future work are concluded in the last section of the report. The recorded FYP Demonstration video is presented in Appendix C.